Pemanfaatan Token dalam Pengembangan Sistem Informasi Barter Barang Berbasis Web Menggunakan Framework Laravel - Firmansyah, Devie; Purwanto, Heri; Wiharko, Teguh; Gustian, Robby (Masoem University, 2023)
Barter is an activity of exchanging goods that do not use money as a medium of exchange. There are several problem that occur in bartering activities, such as the difficulty of finding people who also want to exchange at the same time and the difficulty of determining the value of the goods to be exchanged. The purpose of this research is to develop an information system that can be used as a place for bartering, where the owner can determine the value of the goods to be exchanged. The methodology used in the development of this system is the Agile method, with the modeling language used is UML (Unified Modelling Language). In this study, literature study data collection techniques were also used to collect data regarding the barter system. The result of this research is a web-based goods barter information system that was built using the Laravel Framework by developing a token system from previous research, where the token in this system is used to determine the value of an item as well as a medium of exchange between goods. Based on the test results, the use of tokens as a medium of exchange can help the owner of the goods to determine the value of the goods according to their wishes and make it easier for users to exchange their belongings for other goods.